Transformation of detritus by a European native and two invasive alien freshwater decapods - Doherty-Bone, Thomas M. (Biol Invasions, 2018)
Invasive alien species have the potential to alter biodiversity and ecosystem processes. In freshwaters, detritus decomposition is a major ecosystem service but it remains uncertain whether invasive alien decapods process detritus differently to natives. This study examined leaf litter processing, and cascading effects on biofilms, by the European native white clawed crayfish (Austropotamobius pallipes) compared to two invasive alien decapod species: the American signal crayfish (Pacifastacus leniusculus) and the Chinese mitten crab (Eriocheir sinensis). Invasive alien decapods were responsible for higher leaf litter decomposition than the native. In comparison with native crayfish, invasive alien crab and crayfish showed higher rates of litter consumption, increased production of smaller leaf fragments, fine particulate organic matter (FPOM) and dissolved organic carbon. Nutrients (ammonia and soluble reactive phosphorous) derived from excretion (measured separately in the absence of biofilms) varied among decapod species, being lower for P. leniusculus. However, nutrient concentrations did not vary among species in the detritivory experiments with biofilm, implying nutrients were utilised for biofilm production and respiration as no differences in biomass were evident among decapod treatments. These results show invasive alien decapods have the potential to increase the magnitude of detrital processing to FPOM in rivers, but indirect impacts on primary producers due to nutrient release are uncertain based on this experimental context. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10530-018-1661-z) contains supplementary material, which is available to authorized users.